Efektivitas Kinerja Badan Pengawas Pemilu dalam Pengawasan Kampanye pada Pemilu Tahun 2019 (Studi pada Kantor Bawaslu Kabupaten Konawe) - Nartin, Nartin; Meliyanti, Meliyanti (Jurnal Ilmiah Dikdaya, 2022)
This study aims to determine and describe the effectiveness of Bawaslu's performance in monitoring campaigns in the 2019 elections and how the forms of supervision in the 2019 elections are. The type of data used in this study is qualitative data and the data sources in this study are primary data and secondary data. The results of this study indicate that the supervisory performance carried out by the Konawe Regency Bawaslu in the 2019 election has run effectively, because in carrying out its performance the Konawe Regency Bawaslu has met the benchmark of performance effectiveness by achieving safe elections. The effectiveness of the Konawe Regency Bawaslu performance can be seen from the data on findings of alleged violations in which Bawaslu has succeeded in carrying out surveillance and prevention actions against fraudulent acts during the campaign period, but the constraint for Konawe Regency Bawaslu is the lack of participation and public awareness of supervision so that Konawe Regency Bawaslu and all staff under them must be more observant in carrying out supervision because people who know about fraud that occurred during the campaign they remain indifferent and do not report the matter to the Konawe Regency Bawaslu. And as for the forms of supervision in the 2019 election, it has been carried out optimally in accordance with the forms of supervision which consist of preliminary supervision of supervision during the activity, and feedback monitoring, so that the implementation of the election can run safely and avoid all forms of fraud. that happened.